Wax on, wax off, or whatever works for you : on the role of pre-competition emotions in elite karateka - Amsbury, Kyler (2015)
The purpose of the current study aimed to examine the performance related experiences of elite karate athletes prior to a major international competition. The secondary aim was to explore the relationship between athlete and coach performance ratings.